The Influence of Individual and Contextual Socioeconomic Status on Obstetric Care Utilization in the Democratic Republic of Congo: A Population‑based Study - Aremu, Olatunde; Lawoko, Stephen; Dalal, Koustuv (International Journal of Preventive Medicine, 2012)
Maternal health care utilization continues to focus on the agenda of health care planners around the world, with high attention being paid to the developing countries. The devastating effect of maternal death at birth on the affected families is untold. This study examines the utilization of obstetric care in the Democratic Republic of Congo. Methods: We have used the nationally representative data from the 2007. Democratic Republic of Congo Demographic and Health Survey. Multilevel regression analysis has been applied to a nationally representative sample of 6,695 women, clustered around 299 communities in the country. Results: The results show that there are variations in the use of antenatal care and delivery care. Individual‑level characteristics, such as women’s occupation and household wealth status are shown to be associated with the use of antenatal care. Uptake of facility‑based delivery has been seen to be dependent on the household wealth status, women’s education, and partner’s education. The effect of the neighborhoods’ socioeconomic disadvantage on the use of antenatal care and facility‑based delivery are the same. Women from highly socioeconomically disadvantaged communities, compared to their counterparts from less socioeconomically disadvantaged neighborhoods, are less likely to utilize both the antenatal services and healthcare facility for child delivery. The result of this study has shown that both individual and contextual socioeconomic status play an important role in obstetric care uptake. Conclusion: Thus, intervention aimed at improving the utilization of obstetrics care should target both the individual economic abilities of the women and that of their environment when considering the demand side.
Keywords: Healthcare; Obstetrics; Socioeconomic; Utilization; Congo DRC